COMUNICAÇÃO, TECNOLOGIA E LONGEVIDADE - MUCCI, RICARDO (2018)
Every living being uses a specific language to communicate, from the most rudimentary to the most complex, such as dolphins and elephants, for example. Plants, insects, animals, all communicate in some way, but no species has ever seen such an amazing evolution as humans. This is because homo sapiens is provided with a thinking brain, which allows it to reason and interfere in the reality that surrounds it, as well as to establish forms of language to communicate its actions through diverse means: figurative, sonorous, gestural, manual and electronic. This quality has brought us to the present times, where man conceived a machine that thinks, learns and can replace it in the accomplishment of numerous tasks. A device that uses a digital language integrated with an artificial intelligence, which enables communication between machines and humans and vice versa. The futurists, however, go beyond: they dare to affirm that one day the communication will be mental, without intermediation of any device. In this dissertation, we focus attention on a specific aspect of the communication process, to identify where and how communication technologies can contribute to the quality of life of the elderly population, whether in interpersonal relationships, socialization, learning, entertainment or even to help physical or cognitive limitations. This is because the increase of life expectancy is driving the human being to face the challenge of building and prolonging a healthy and productive life and in this context communication is vital. To reach this contextual stage, we have built a trajectory that includes the evolution of on and off-line media, the impact of computational technologies, the advances of science in the study of the functioning of the brain, until we reach virtual reality and artificial intelligence, which are innovations capable of generating exponential transformations in the relationship between men and machines. Studies on the impacts of science and technology on longevity have gained such relevance in recent years that they have emerged a new area of knowledge called Gerontechnology, which also includes the research and development of new products and communication processes that should contribute decisively to the integration and the socialization of the elderly population in Brazil and all the world.